Motivations in weight reduction and undesirable eating behaviors among women with excessive body weight (Poland) - Krupa-Kotara, Karolina; Grajek, Mateusz; Kulesza, Aleksandra; Yanakieva, Antoniya; Sas-Nowosielski, Krzysztof (Journal of Education, Health and Sport, 2022)
The aim of this study was to evaluate the relationship between attitudes toward weight loss, taking into account: the motivating factors that determine the desire to attempt weight loss; the level of well-being and degree of motivation before and during the weight loss attempt; changes in attitudes after an unsuccessful weight loss attempt; the state of well-being after the completed weight loss attempt and the degree of severity of disordered eating according to the TFEQ-13 questionnaire. The study was conducted among 600 female users of forums for people with excessive weight. The research method used in this study was the author's questionnaire and the standardized Three-Factor Eating Questionnaire. A general survey questionnaire serving as a working tool was sent by Computer-Assisted Web Interview to community groups. The predominant group of respondents cannot even count the weight reduction attempts they have made during their lives (31%). Three attempts were made by 29% of respondents, and two attempts by 17%. Attempts to lose weight most often involved increasing current physical activity (overall responses), reducing the caloric content of meals (26%), and improving current eating habits (22%). Most people reduced their body weight from 6 kg to 10 kg (29%) or from 3 to 5 kg (27%). It was found that low a risk of aggravation was diagnosed in 45.5% of people, moderate in 44.5, and low in 10%. For lack of control over eating – a low risk was observed in 15.5% of people, moderate in 68.5% of people, and high in 16%. Evaluating eating under the influence of emotions, the highest risk of the studied phenomenon was observed in 50.5% of people, moderate risk in 36.5% of people, and low risk in 13% of people. The level of motivation significantly decreased when trying to reduce weight. No significant deterioration in well-being was observed before and during the weight loss attempt.